Identitas Keturunan Perempuan Dalam Kejadian 3:15 Dalam Studi Soteriologi - Pangeran Manurung (Jurnal Teologi dan Pelayanan Kerusso, 2020)
One of the problems arising from the polemic of the events of the fall of man in the Garden of Eden recorded by the author of the Book of Genesis is the bias of the policy of salvation taught by the writers of the New Testament. Salvation in the New Testament is considered not to have originated in the Old Testament mind. Apart from the element of salvation in the Old Testament which is only supposed to contain "political" salvation, the clarity of the interpretation of the female offspring and its fulfillment in Jesus Christ is also questioned. Jesus Christ is considered unqualified as a descendant of the woman offended in Genesis 3 so that the eternal salvation offered by Jesus Christ in the event of the crucifixion is considered an offer of a "concept of salvation" that is not in line with the promise of salvation in Genesis 3. While other commentators state the opposite. This study will discuss it using a biblical library research approach. This means that the researcher will prove who the offspring of the woman referred to in incident 3 is based on the evidence from the Old and New Testaments. The results of this study prove that the female offspring referred to in event 3 is Jesus Christ. The phrase “bruising in the heel” in the pericope is a symbolic statement of the crucifixion event of Jesus Christ which is interpreted by New Testament readers as the salvation promised in Genesis 3:15. Abstrak Indonesia Salah satu permasalahan yang ditimbulkan dari polemik peristiwa kejatuhan manusia di Taman Eden yang dicatat oleh punulis Kitab Kejadian adalah biasnya dasar keselamatan yang diajarkan oleh penulis Perjanjian Baru. Keselamatan dalam Perjanjian Baru dianggap tidak bersumber dari pikiran Perjanjian Lama. Selain karena unsur keselamatan dalam Perjanjian Lama yang hanya diduga mengandung keselamatan secara “politis”, kejelasan penafsiran terhadap keturunan perempuan dan penggenapannya dalam diri Yesus Kristus juga dipertanyakan. Yesus Kristus dianggap tidak memenuhi syarat sebagai keturunan perempuan yang disinggung dalam Kejadian 3 sehingga keselamatan kekal yang ditawarkan oleh Yesus Kristus dalam peristiwa penyaliban dianggap sebagai sebuah tawaran “konsep keselamatan” yang tidak sehaluan dengan janji keselamatan dalam Kejadian 3. Sementara penafsir yang lain menyatakan kebalikannya. Penelitian ini akan membahasnya dengan menggunakan pendekatan penelitian kepustakaan yang bersifat biblika. Artinya peneliti akan membuktikan siapa keturunan perempuan yang dimaksud dalam kejadian 3 berdasarkan bukti dari Perjanjian Lama dan Perjanjian Baru. Hasil dari penelitian ini membuktikan bahwa keturunan perempuan yang dimaksud dalam kejadian 3 adalah Yesus Kristus. Frase “meremukkan tumit” dalam perikop merupakan pernyataan simbolis atas peristiwa penyaliban Yesus Kristus yang dimaknai oleh para pembaca Perjanjian Baru sebagai keselamatan yang dijanjikan dalam Kejadian 3:15.